Association of volume of self-directed versus assigned interpretive work with diagnostic performance of radiologists: an observational study - Shiori Amemiya; Harushi Mori; Hidemasa Takao; Osamu Abe (BMJ Open)
Objectives To understand the sources of variability in diagnostic performance among experienced radiologists.Design All prostate MRI examinations performed between 2016 and 2018 were retrospectively reviewed.Setting University hospital in Japan.Participants Data derived from 334 pathology-proven cases (male, mean age: 70 years; range: 35–90 years) that were interpreted by 10 experienced radiologists were subjected to the analysis.Primary and secondary outcome measures Diagnostic performance measures of the radiologists were compared with candidate factors, including interpretive volume of prostate MRIs, volume of self-directed and assigned total annual interpretive work, and years of experience. The potential influence of fatigue was also evaluated by examining the effect of the report’s issue time.Results There were 186 prostate cancer cases. Performance was based on accuracy, sensitivity and specificity (86%, 85% and 84%, respectively). While performance was not correlated with the volume of prostate MRIs, per se (ρ=–0.15, p=0.69; ρ=–0.01, p=0.99; ρ=–0.33, p=0.36) or the total MRIs assigned for each radiologist (p>0.6) or years of experience (p>0.4), all measures were strongly correlated with voluntary work represented by the interpretive volume of abdominal CTs (r=0.79, p<0.01; r=0.80, p<0.01; r=0.64, p=0.048). The performance did not differ based on the issue time of the report (morning, afternoon and evening) (χ2(2)=3.65, p=0.16).Conclusions Greater autonomy, represented as enhanced self-directed interpretive work, was most significantly correlated with the performance of prostate MRI interpretation. The lack of a correlation between the performance and assigned volume confirms the complexity of human learning. Together, these findings support the hypothesis that successful promotion of internal drivers could have a pervasive positive impact on improving diagnostic performance.